The Cost of Transacting - Demsetz, Harold (Quarterly Journal of Economics, 1968)
Introduction, 33. — The definition and measurement of transaction cost on the New York stock exchange, 35. — The determination of the ask-bid spread, 40. — The determination of the transaction rate, 45. — Statistical results, 46. — Summary and comments, 50. — Appendix I, 52. — Appendix II, 53.